Wide Awake in the Pelican State : Stories by Contemporary Louisiana Writers - Dobie, Ann B. (Book collections on Project MUSE., 2006)
This collection brings together twenty-one of the finest modern writers who claim Louisiana as home. Contributors include James Lee Burke, Robert Olen Butler, Richard Ford, Ernest J. Gaines, Tim Gautreaux, Tim Parrish, and James Wilcox.